An analysis of the nexus between female labour force participation and women’s empowerment in Bangladesh - Mustafa, Aporajita (Brac University, 2019)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Social Sciences in Economics, 2019.